Advancing sustainable entrepreneurial universities: sustainability transformations of university business incubators in Germany - Marc Karahan (Small Business Economics, 2024)
Given the profound environmental and societal challenges, many higher education institutions (HEI) have adopted sustainability as a central mission to induce desirable societal impacts. While previous research investigated the transformation processes of HEIs toward sustainability, few studies took an explicit entrepreneurial perspective and questioned its implications for the Entrepreneurial University (EU) model. To address this gap, our study explores the emergence and pursuit of a Sustainable Entrepreneurial University (SEU). We specifically focus on the role of sustainable university business incubators (UBIs) as primary institutions of entrepreneurship within the SEU model. Using a multiple-case study of four German UBIs, we illustrate how they embarked on their sustainability journey, developed internal capacities to support sustainable entrepreneurship, and overcame various barriers during their transformation trajectories. Our analysis identifies six distinct sustainability transformation stages and proposes a stylized model to explain the emergence of sustainability in UBIs. Based on these findings, our study discusses several theoretical implications for the SEU. We illustrate that SEU sustainability impacts evolve over time and that continuous leadership commitment is a mediating factor. Moreover, our results suggest that SEUs strategically engage in external partnerships with alternating functions. Given the urgency to promote sustainable entrepreneurship in HEIs, the study concludes with several practical recommendations for practitioners and policymakers. Moreover, it offers suggestions for future research to explore the potential of SEUs and their contribution to addressing pressing societal and ecological challenges.
Keywords: L26; L31; M13; I23; 330; Technology transfer; Sustainable entrepreneurship; Incubator; University entrepreneurship; Academic entrepreneurship